C–H bond activation via concerted metalation–deprotonation at a palladium(iii) center. Issue 14 (17th March 2023) - Bouley, Bailey S.; Tang, Fengzhi; Bae, Dae Young; Mirica, Liviu M.
Abstract : Herein we report the direct observation of C–H bond activation at an isolated mononuclear Pd(iii ) center. Abstract : Herein we report the direct observation of C–H bond activation at an isolated mononuclear Pd(iii ) center. The oxidation of the Pd(ii ) complex ( Me N4)Pd II (neophyl)Cl (neophyl = –CH2 C(CH3 )2 Ph; Me N4 = N, N ′-dimethyl-2, 11-diaza[3.3](2, 6)pyridinophane) using the mild oxidant ferrocenium hexafluorophosphate (FcPF6 ) yields the stable Pd(iii ) complex [( Me N4)Pd III (neophyl)Cl]PF6 . Upon the addition of an acetate source, [( Me N4)Pd III (neophyl)Cl]PF6 undergoes Csp 2 –H bond activation to yield the cyclometalated product [( Me N4)Pd III (cycloneophyl)]PF6 . This metalacycle can be independently prepared, allowing for a complete characterization of both the starting and final Pd(iii ) complexes. The C–H activation step can be monitored directly by EPR and UV-Vis spectroscopies, and kinetic isotope effect (KIE) studies suggest that either a pre-association step such as an agostic interaction may be rate limiting, or that the C–H activation is partially rate-limiting in conjunction with ligand rearrangement. Density functional theory calculations support that the reaction proceeds through a κ 3 ligand coordination and that the flexible ligand structure is important for this transformation. Overall, this study represents the first example of discrete C–H bond activation occurring at a Pd(iii ) center through a concerted metalation–deprotonation mechanism, akin to that observed for Pd(ii ) and Pd(iv ) centers.